Elevating Virtual Reality Experiences with Olfactory Integration: A Preliminary Review - da Silva, Meryck Felipe Brito; Sanches, Igor Henrique; Borba, Joyce Villa Verde Bastos; Barros, Ana Carolina de Amorim; Feitosa, Francisco Lucas; de Carvalho, Rodrigo Mendes; Filho, Arlindo Rodrigues Galvão; Andrade, Carolina Horta (Journal of the Brazilian Computer Society, 2024)
Virtual reality (VR) provides immersive audio-visual experiences but often overlook olfactory senses, which are crucial for human perception and cognition. Smell enhances object recognition, visual spatial attention, and evaluation methods for spatial attention deficits. The sense of smell relies on the olfactory nerve to create a direct link between external stimuli and the limbic system, a brain network involved in regulating emotions such as sadness, anger, joy, and fear, as well as controlling physiological responses like the startle reflex, vocal intonation, pain perception, and memory processes. Artificial intelligence (AI) is essential for integrating odors into VR, enhancing contextual understanding and synchronizing smells with plot developments. Current multi-modal approaches highlight the need for integrated models combining images, texts, and smells. Olfactory cues can enhance memory retention and recall, benefiting educational and training applications. Incorporating scents into immersive technologies creates more realistic and engaging experiences, crucial for fields like healthcare, military training, and education. In this preliminary review, we will explore Olfactory Virtual Reality (OVR) technologies, AI applications, available devices, and future perspectives in the field. Additionally, we will discuss the challenges facing this technology, including issues of delay, size, and the limited range of available odors. A new wearable interface featuring miniaturized odor generators (OGs) and AI algorithms enables rapid responses and low power consumption, achieving latency-free mixed reality. OVR research shows promising applications in treating Post-Traumatic Stress Disorder (PTSD), alleviating anxiety, and enhancing immersion. Recent advancements, such as compact OGs and computer-controlled olfactory stimulation, represent significant progress in multisensory communication technology.